SEXUAL ADDICTION IN THE WORKPLACE: An EAP Perspective. - Turner-Shults, Nanci; Shults, Charley (Sexual Addiction & Compulsivity, 1997)
This article examines sexual addiction from an employee assistance perspective. An attempt is made to identify problems caused by sexual addiction in the workplace through the use of case studies and discussion. Suggested solutions include taking appropriate action to identify, intervene with, and get help for employees who are sexually addicted.